2017
DOI: 10.1021/acs.biochem.6b00954
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Profiling Approach to Inhibitors of the Orphan M. tuberculosis P450 CYP144A1

Abstract: Similarity between the ligand binding profiles of enzymes may aid functional characterization and be of greater relevance to inhibitor development than sequence similarity or structural homology. Fragment screening is an efficient approach for characterization of the ligand binding profile of an enzyme and has been applied here to study the family of cytochrome P450 enzymes (P450s) expressed by Mycobacterium tuberculosis (Mtb). The Mtb P450s have important roles in bacterial virulence, survival, and pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…High sensitivity and simple instrumentation, with no special requirements for experimental conditions, make UV-VIS spectroscopy a method of choice for thermodynamic and kinetic studies of cytochromes P450, as well as when employing cryogenic methods, [38,41,59,60,76,95] high pressure, [96,97,98,99] flash photolysis and photoacoustic methods in nanosecond range, [100,101,102,103,104] etc. Optical absorption spectra can be used for monitoring binding mode and for comparing substrate analogs, [105,106,107] or binding of the same substrate to single point mutants. [7,23,108,109] In addition, spectral changes can be used for direct observation of allosteric effects in substrate binding.…”
Section: Substrate Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…High sensitivity and simple instrumentation, with no special requirements for experimental conditions, make UV-VIS spectroscopy a method of choice for thermodynamic and kinetic studies of cytochromes P450, as well as when employing cryogenic methods, [38,41,59,60,76,95] high pressure, [96,97,98,99] flash photolysis and photoacoustic methods in nanosecond range, [100,101,102,103,104] etc. Optical absorption spectra can be used for monitoring binding mode and for comparing substrate analogs, [105,106,107] or binding of the same substrate to single point mutants. [7,23,108,109] In addition, spectral changes can be used for direct observation of allosteric effects in substrate binding.…”
Section: Substrate Bindingmentioning
confidence: 99%
“…Other examples of NMR application to studies of substrate binding and for structural evaluation of substrate positioning and dynamics in P450 catalytic site have been described. [106,191,192]…”
Section: Substrate Bindingmentioning
confidence: 99%
“…A fragment profiling approach was pursued in efforts to obtain a clue to the native substrate, but the results did not yield a specific identity. However, they may be useful if the further development of inhibitors for the enzyme is warranted (57)…”
Section: Cyp144mentioning
confidence: 99%
“…For example, the family of cytochrome P450 enzymes (P450s) play important roles in Mycobacterium tuberculosis . Using fragment screening, Kavanagh et al [86] identified similarities in the ligand-binding profile of CYP121A1, which is known to be important for M . tuberculosis viability, and the orphan enzyme CYP144A1.…”
Section: Drug-based Approachesmentioning
confidence: 99%
“…tuberculosis viability, and the orphan enzyme CYP144A1. An assessment of the similarities and differences in binding between the two enzymes provides insight into both the function of the enzyme and potential inhibitors [86].…”
Section: Drug-based Approachesmentioning
confidence: 99%